The membrane-associated transcription factor NAC089 controls ER-stress-induced programmed cell death in plants. - Zheng-Ting Yang; Mei-Jing Wang; Ling Sun; Sun-Jie Lu; Dong-Ling Bi; Le Sun; Ze-Ting Song; Shuang-Shuang Zhang; Shun-Fan Zhou; Jian-Xiang Liu (PLoS Genetics, 2014)
The unfolded protein response (UPR) is activated to sustain cell survival by reducing misfolded protein accumulation in the endoplasmic reticulum (ER). The UPR also promotes programmed cell death (PCD) when the ER stress is severe; however, the underlying molecular mechanisms are less understood, especially in plants. Previously, two membrane-associated transcriptions factors (MTFs), bZIP28 and bZIP60, were identified as the key regulators for cell survival in the plant ER stress response. Here, we report the identification of another MTF, NAC089, as an important PCD regulator in Arabidopsis (Arabidopsis thaliana) plants. NAC089 relocates from the ER membrane to the nucleus under ER stress conditions. Inducible expression of a truncated form of NAC089, in which the transmembrane domain is deleted, induces PCD with increased caspase 3/7-like activity and DNA fragmentation. Knock-down NAC089 in Arabidopsis confers ER stress tolerance and impairs ER-stress-induced caspase-like activity. Transcriptional regulation analysis and ChIP-qPCR reveal that NAC089 plays important role in regulating downstream genes involved in PCD, such as NAC094, MC5 and BAG6. Furthermore, NAC089 is up-regulated by ER stress, which is directly controlled by bZIP28 and bZIP60. These results show that nuclear relocation of NAC089 promotes ER-stress-induced PCD, and both pro-survival and pro-death signals are elicited by bZIP28 and bZIP60 during plant ER stress response.